A PENERAPAN QAWAIDUL AHKAM DALAM PENEYLESAIAN SENGKETA PERCERAIAN STUDI KASUS PENGADILAN AGAMA RANGKASBITUNG: PENERAPAN QAWAIDUL AHKAM DALAM PENYELESIAN SENGKETA PERCERAIAN USIA MUDA AKIBAT KDRT STUDI KASUS DIPENGADILAN AGAMA RANGKASBITUNG - Heni, Heni Rohaeni; Tarihoran, Nafan; Asfandi (Syakhsia Jurnal Hukum Perdata Islam, 2024)
Divorce at a young age, where a husband and wife divorce before reaching the age of 26has become a social phenomenon that is increasingly worrying in various countries,including Indonesia. Qawaidul Ahkam, Islamic Law Guidelines, offers an approach toresolving young divorce disputes. This discussion is about the application of QawaidulAhkam by emphasizing mediation, the principles of justice and kindness of religiousfigures, families, communities and Islamic law.Qawaidul Ahkam's approach prioritizes dialogue and peaceful solutions, considering thebest interests of children and upholding Islamic values. Religious, family and communityleaders have an important role in providing support and guidance. The application ofIslamic law must be carried out sensitively and contextually, and prioritize justice andhumanity. Preventing young divorce requires comprehensive and multi-sectoral efforts.Qawaidul Ahkam offers a framework based on Islamic values to help resolve youngdivorce disputes fairly and constructively.Based on qualitative descriptive research methods and a sociological normativeapproach, it can be concluded that divorce at a young age is permissible even in Islam.If a young couple experiences very severe incompatibility and cannot be resolved throughmediation or counseling, then divorce can be the final solution.